Assistance for Pregnant Women and Families in Early Detection of Preeclampsia (PE) and Early Referral Planning as an Effort to Prevent Complications - Deasy Irawati (Frontiers in Community Service and Empowerment, 2023)
The purpose the activity is to increase the participation of pregnant women and families in early detection of Preeclampsia (PE) risk and early referral planning as an effort to prevent complications. The methods are carried out in several stages, namely pregnancy health education with PE, early detection screening by health workers using the 2020 MCH book guidelines (risk factor history, as well as BMI, Mean Arterial Pressure and urine protein checks. If the screening results found the risk of PE or diagnosed PE (BP ≥ 140/90 mmHg and positive urine protein) then followed by reporting to the local midwife, motivating the mother for early referral action planning and assistance during pregnancy. Results: knowledge of pregnant women and families about PE increased from 67% in the poor category, after receiving information 92% in the good category. Early detection screening by health workers using the 2020 MCH book guidelines, out of 12 pregnant women, 2 people (16.7%) had a risk of PE and 10 people (83.3%) did not have a risk of PE. None of the pregnant women were diagnosed with PE. 2 pregnant women who have the risk of PE (100%) have been reported to the Kapor village midwife and are willing to be referred to the Burneh Puskesmas. There is an increase in community participation (pregnant women and families) in early detection of PE and early referral planning as an effort to prevent complications.